2012
DOI: 10.1159/000337459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antipsychotic Agents on Heart Rate Variability in Male WKY Rats: Implications for Cardiovascular Safety

Abstract: Background: Sudden cardiac death is higher among schizophrenic patients and is associated with parasympathetic hypoactivity. Antipsychotic agents are highly suspected to be a precipitating factor. Thus, we aimed to test if the antipsychotics haloperidol, risperidone and clozapine affect cardiac autonomic function, excluding the confounding effect of altered sleep structure by the drugs. Methods: In this study, haloperidol, risperidone and clozapine were given separately by intraperitoneal injection to male Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Of note, only animals treated with CLZ displayed significantly different RR, TP, and LF% values compared to controls regardless of consciousness. HAL and risperidone did not significantly influence HRV in the same manner as CLZ, which the authors attributed to CLZ's strong anticholinergic and antiadrenergic properties (Wang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Of note, only animals treated with CLZ displayed significantly different RR, TP, and LF% values compared to controls regardless of consciousness. HAL and risperidone did not significantly influence HRV in the same manner as CLZ, which the authors attributed to CLZ's strong anticholinergic and antiadrenergic properties (Wang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 95%
“…The sole HRV preclinical study identified in our literature search was conducted by Wang et al ( 2012 ), on male Wistar-Kyoto rats. This study also took into consideration the influence of antipsychotics on sleeping patterns and consequently autonomic activity during sleep-wake cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-sample t-tests were used to analyze the differences between the delta value and baseline. The effects of the two factors (ambient temperature and sleep stage) on changes of autonomic activities were assessed by two-way mixed design ANOVA (two ambient temperatures × two sleep stages) [33]. When pinpointed by a significant F-statistic, the differences between states were isolated using post-hoc comparisons and Fisher's least-significant difference test.…”
Section: Discussionmentioning
confidence: 99%
“…Polypharmacy is strongly associated with excessive dosing and early death (Ito et al ., 2005[16]). Use of thioridazine is a predictor of QTc prolongation, and even moderate doses of antipsychotics would increase the risk of sudden cardiac death (Wang et al ., 2012[55]). Antipsychotic polypharmacy, compared with monotherapy, is found to be independently associated with an increased risk of having pre-metabolic syndrome, even after adjusting for patients’ lifestyle characteristics (Misawa et al ., 2011[27]).…”
Section: Introductionmentioning
confidence: 99%